1994
DOI: 10.1111/j.1432-1033.1994.tb19052.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an alkaline elastase from Myxococcus xanthus

Abstract: An extracellular elastase, termed Myxococcus xanthus alkaline protease 1 (MAPl), has been purified from M. xanthus DK1622 culture supernatants by a combination of ion-exchange and affinity chromatographies. It consists of a single peptide chain of 39 kDa. The elastolytic activity was totally suppressed by 10 mM 1,lO-phenanthroline and the enzyme may then be classified as a metalloprotease. Its pH optimum was estimated to be 8.2 with both elastin-orcein and succinyl-Ala, p-nitroanilide as substrates. Despite it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…To our knowledge, this enzyme is the first reported elastase in family M12. The cleavage pattern of myroilysin with the oxidized insulin B chain also showed that it had broad specificity and that it shared some, but not all, cleavage sites with pseudolysin and porcine pancreatic elastase (8). These results show the difference between myroilysin and pseudolysin in terms of substrate specificity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…To our knowledge, this enzyme is the first reported elastase in family M12. The cleavage pattern of myroilysin with the oxidized insulin B chain also showed that it had broad specificity and that it shared some, but not all, cleavage sites with pseudolysin and porcine pancreatic elastase (8). These results show the difference between myroilysin and pseudolysin in terms of substrate specificity.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported that animal elastase has a synergistic effect with collagenase in collagen degradation (27,34). Although some bacterial elastases have been studied (8,18,31), there has been no report that a bacterial elastase has a synergistic effect with collagenase in collagen degradation. Myroilysin did not readily hydrolyze type I collagen fiber, yet its collagen-swelling activity exceeded that of 6 M urea.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage at two sites in the oxidized insulin ␤-chain predominated at 1 and 30 min following the addition of low amounts of alkaline protease (24,41,46,47). At 1 min, cleavage of the Leu 15 -Tyr 16 and Phe 24 -Phe 25 bonds generated peptides containing residues 16 -30 and 25-30 with a yield of 15 and 12%, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Mammalian elastase is characterized by its cleavage specificity for small hydrophobic amino acids such as alanine. In contrast, bacteria produce a wide variety of proteases with elastolytic activity including metalloproteases (24,25) and members of both the bacterial serine enzyme superfamilies (26 -28). These proteases have cleavage specificities that include bulky, as well as small, hydrophobic amino acids.…”
mentioning
confidence: 96%
“…Although it is known that numerous extracellular proteins are produced during vegetative growth, few have been characterized or purified so far, and these are mainly lytic enzymes such as cell wall lytic enzymes (35) and proteases (4,6,9,21,29). Recently, it has been established (31) that some secreted trypsin-like proteases from M. xanthus were a component of the above-mentioned A factor, a complex mixture of amino acids, peptides, and proteases which induces the differentiation pathway of this bacterium after starvation.…”
mentioning
confidence: 99%